2011
DOI: 10.1186/1471-2334-11-87
|View full text |Cite
|
Sign up to set email alerts
|

Did the pandemic have an impact on influenza vaccination attitude? a survey among health care workers

Abstract: BackgroundHealth care workers' (HCWs) influenza vaccination attitude is known to be negative. The H1N1 epidemic had started in mid 2009 and made a peak in October-November in Turkey. A national vaccination campaign began on November 2nd, 2009. Despite the diligent efforts of the Ministry of Health and NGOs, the attitudes of the media and politicians were mostly negative. The aim of this study was to evaluate whether HCWs' vaccination attitudes improved during the pandemic and to assess the related factors.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 22 publications
6
42
1
3
Order By: Relevance
“…For the health group, one of the significant determinants of willingness to receive the Influenza A(H1N1) vaccine was previously being vaccined against seasonal influenza (O.R: 2.9 [1.5-5.6]).This result was similar to the study of Pfeil A et Table 3 al [20,21]. Like willingness, it was determined that seasonal influenza was also an important factor to beleive in the vaccine.…”
Section: Discussionsupporting
confidence: 80%
“…For the health group, one of the significant determinants of willingness to receive the Influenza A(H1N1) vaccine was previously being vaccined against seasonal influenza (O.R: 2.9 [1.5-5.6]).This result was similar to the study of Pfeil A et Table 3 al [20,21]. Like willingness, it was determined that seasonal influenza was also an important factor to beleive in the vaccine.…”
Section: Discussionsupporting
confidence: 80%
“…Similar acceptance rates for vaccination have been reported in other studies among the general population (Mexico 80% [28], Canada 69% [29] and 75% [30], and 89% in Kenya [31]). However, our results are markedly different from those in other studies that have reported a low willingness to be vaccinated in HCPs [13][14][15][32][33][34][35]. This difference could be explained by the period at which certain studies were conducted, especially under the influence of the evolution of the pandemic.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, the Ivorian health authorities had not released any specific information about the vaccine against pandemic influenza A (H1N1) to health-care providers; this situation posed a real risk in implementing a successful vaccination campaign [4][5][6][7]. Reports questioning the efficacy and safety of the pandemic vaccine [8][9][10][11][12] led to low vaccination coverage in health-care providers in some countries [13][14][15]. In Sub-Saharan Africa, there was a general lack of data on influenza, including both epidemiological data as well as data on seasonal vaccination against influenza [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in our country it was found that the most frequent reasons for not getting a vaccination with pandemic influenza vaccine were the fear of the side effects of the vaccine and the lack of adequate studies on the vaccine [18]. Again in a study performed in Greece, though 97% of healthcare providers accept the importance of vaccination, only 17% were reported to have a vaccination with pandemic influenza vaccine [19].…”
Section: Resultsmentioning
confidence: 99%